Determination of systemically important companies with cross-shareholding network analysis: A case study from an emerging market - Hossein Dastkhan; Naser Shams Gharneh (International Journal of Financial Studies, 2016)
Systemic risk events constitute an important issue in current financial systems. A leading course of action used to mitigate such events is identification of systemically important agents in order to implement the prudential policies in a financial system. In this paper, a bi-level cross-shareholding network of the stock market is considered according to direct and integrated ownership structure. Furthermore, different systemic risk indices are applied to identify systemically important companies in an early warning system. Results of application of these indices on cross-shareholding data from Tehran Stock Exchange show that integrated network indices produce more reliable results. Moreover, results of statistical analysis of the networks indicated the existence of scale-free characteristics in the TSE cross-shareholding network.
Keywords: C6; E44; G10; G18; G32; 330; finance; network theory; systemic risk; cross-shareholding; centrality measures